K=(4x-2)-7

Simple and best practice solution for K=(4x-2)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for K=(4x-2)-7 equation:



=(4K-2)-7
We move all terms to the left:
-((4K-2)-7)=0
We calculate terms in parentheses: -((4K-2)-7), so:
(4K-2)-7
We get rid of parentheses
4K-2-7
We add all the numbers together, and all the variables
4K-9
Back to the equation:
-(4K-9)
We get rid of parentheses
-4K+9=0
We move all terms containing K to the left, all other terms to the right
-4K=-9
K=-9/-4
K=2+1/4

See similar equations:

| 6x^2-25x-12=0 | | 9z-6=23z-14 | | 8y(2y+4)=102 | | x^2+11/2x=1/2 | | 12x-12=6(3x) | | (5x/2)−4=(2x−7/6) | | 2y+4=-18-9y | | 7+4(3x-6)=-5(2x+1) | | 9y+53=8 | | 27.79=5g+3.94 | | x^2+10=54 | | 4y+53+5y=26+ | | 5x+4Y=95 | | 4x/3-1=19 | | 6/11=36x | | 1/2(6+-z)=z | | 35=4v+8 | | 31.64=6g+3.74 | | 76=20+7c | | 11x-(6×-5)=40 | | 3(4z-7)=-21=12z | | 3/4x-1/3=1/4x+2/3 | | t(t+1)^2−2t/(t+1)−80=0 | | 2n-5n=2/6 | | 40x+5(1.25x)=555 | | 15+x=30+0.1x | | 11x-(9x-7)=13 | | b-7b=24 | | 2(-8a+6)=-116 | | 79x+15)=126 | | 10m+9=-10 | | 51=33-3(x-1) |

Equations solver categories